Análise da sustentabilidade na produção familiar no Sudeste Paraense: o caso dos produtores de leite do Município de Rio Maria - FEITOSA, Terezinha Cavalcante (2003)
This study analyzes the sustainability of milk production in smallholder areas subjected to the process of fast degradation of pastures established in upland areas (terra firme) in the border of the Brazilian Amazonia. The research was carried out in the Municipality of Rio Maria, Southeast of the State of Pará, one of the Municipalities internationally recognised for its high degree of land conflicts. Fifty-five smallholders in the Settlement Projects of Itaipavas 126, Barra Mansa, Mata Azul, Fazenda São Roque and Vale da Serra, who are sustained by cattle milk production, were interviewed during the months of July and August of 2002. The choice of the properties was intentional, and it was composed by the identification of the income from the cattle raising activities (sale of milk and heifers), as well as an analysis of the techniques used by the smallholders for pasture and livestock management, aiming the sustainability of the productive unit.That analysis allowed to identify, through the socioeconomic indicators, that, although cattle ranching is considered a low risk activity, economically viable for the Amazon region, among the smallholders it becomes an unsustainable activity, because the process of pasture degradation starts within three to five years of pasture establishment, without, however, allowing the production units to save economic resources for pastures reclamation.The sustainable income of livestock milk production activity, being very low relative to the income obtained soon after the initial phase of the activity, does not stimulate the adoption of more sustainable practices. The declining tendency of pasture productivity, with small short term increases, caused by pasture burning and weed control, has been compensated by the incorporation of new areas of pasture. The exhaustion of forest stocks leads to the collapse of the activity in spite of the existing market for meat and milk, when degraded pastures are not reclaimed. Considering an annual rate of pasture depreciation of 10% and an annual interest rate of 15%, farmers would have to invest at least 40% of their net profit to guarantee the pasture sustainability at a ten-year period. It was observed that the livestock milk production activities conducted by smallholders is causing a continuous drainage of the natural resources, without the due compensation in the sale price of those products (milk and beef). It is expected that these results can contribute to define public policies, with concrete measures for the smallholders involved in milk production in the sense of guaranteeing the reclamation of degraded pastures, because these smallholders are responsible for a great part of the ecological disbalance of the ecosystem in the Southeast of Pará State. Among the resource-poor cattle farmers there is no financing need for continuous acquisition of cattle, because all the farmers already possess livestock above the holding capacity of their pastures. In that case, it would be necessary instructing the farmers aiming the proper management of the herd and pasture and the creation of financing programs, aiming the recovery of degraded pasture areas. Among the farmers studied does not exist a conservation view, but rather, an anxiety to increase the herd size and pasture areas.